PENGARUH MODEL PEMBELAJARAN COOP-COOP TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 19 PALEMBANG - Yuli Ambarwati; Dewi Koryati; Deskoni Deskoni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
This study aims to test the influence of Coop-Coop Model on Student Learning Interest in Economic Subject in SMA Negeri 19 Palembang. The research problem is "is there any influence of Coop-Coop model on the interest of learners on economic subjects in SMA Negeri 19 Palembang". This research is an experimental research, which uses Pre-experimental design design, with the form of One Group pretest posttest. The population in this research is all class XI IPS in SMA Negeri 19 Palembang which amounted to 174 students. The sample used cluster random sampling, so selected XI IPS 2class of 34 students as experimental class.Data collection techniques used are observations and questionnaires. Observation data collection techniques obtained from teacher observation and interest of learners at the time of learning took place. Hypothesis testing using parametric stasis is product moment coller obtained r = 1. With very strong interpretation, Coefficient of Determination of 100% and t-test obtained value t count ≥ t tabel = 55,58>1,67 so Ha received Ho rejected. So it can be concluded there is influence of Coop-Coop model on the interest of learners on the subjectsEconomic at SMA Negeri 19 Palembang.